Student's Difficulties In Answering Multiple-Choice Questions In Narrative Text At Eight Grade Of SMP Muhammadiyah Karangrayung - Padminingsih, Sri, Drs. DJoko Srijono, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This research is aimed at describing: 1) students' difficulties in answering multiple choice questions in narrative text, and 2) Why do the students have difficulty in answering multiple choice questions of narrative text. In this research is descriptive research as an approach to collect and analyze the data. The object of this research is students' difficulties in answering multiple choice questions at eight grades of SMP Muhammadiyah Karangrayung in 2012/2013 academic year. The method of collecting data conducted by doing: observation, interview, and document analysis. The results of this research show that student' difficulties in answering multiple choice questions, and why do the students have difficulty in answering multiple choice questions in narrative text. The result of students' difficulties in answering multiple choice questions are as follows: 1) main idea, 2) meaning of word or vocabulary, and 3) generic structure. The reason why the students have difficulty in answering multiple choice questions in narrative text are as follows: 1) less interest in following the lesson , 2) the lack of vocabulary, 3) the limitation of time, 4)length of paragraph, 5)and too many choices which are similar to each other in multiple choice questions.